FLEXIBILITY, STRENGTH AND B.M.I. OF DANCERS CLASSICAL (Fiep Bulletin - online, 2013)
We find that much has been said about the history of dance and classical ballet, their creations, their creators and their dancers, but little is known about the morphology and function of these (Silva and Bonorino, 2008). It is because there is little research in the area where the researcher, the dance many years, she was drinking this water source where little leaves. The professionals of dance that are in the market increasingly need to upgrade technical knowledge about their specific areas so that they can diagnose their students there and then try a program suited to these needs. One of the most important and current concerns with humans is related to health, but how do you know, how to prevent it or at least we know what is or what was diagnosed. These are two perspectives that this search is justified. This study deals with an exploratory and descriptive research aims to verify flexibility, strength and B.M.I. for classical dancers to establish a standard and an expectation to be achieved seeking better technical levels.
Keywords: flexibility; strength; B.M.I.